Electric fields of motor and frontal tDCS in a standard brain space: A computer simulation study - Laakso, Ilkka; Tanaka, Satoshi; Mikkonen, Marko; Koyama, Soichiro; Sadato, Norihiro; Hirata, Akimasa (NeuroImage (Orlando, Fla.), 2016)
The electric field produced in the brain is the main physical agent of transcranial direct current stimulation (tDCS). Inter-subject variations in the electric fields may help to explain the variability in the effects of tDCS. Here, we use multiple-subject analysis to study the strength and variability of the group-level electric fields in the standard brain space. Personalized anatomically-accurate models of 62 subjects were constructed from T1- and T2-weighted MRI. The finite-element method was used to computationally estimate the individual electric fields, which were registered to the standard space using surface based registration. Motor cortical and frontal tDCS were modelled for 16 electrode montages. For each electrode montage, the group-level electric fields had a consistent strength and direction in several brain regions, which could also be located at some distance from the electrodes. In other regions, the electric fields were more variable, and thus more likely to produce variable effects in each individual. Both the anode and cathode locations affected the group-level electric fields, both directly under the electrodes and elsewhere. For motor cortical tDCS, the electric fields could be controlled at the group level by moving the electrodes. However, for frontal tDCS, the group-level electric fields were more variable, and the electrode locations had only minor effects on the group average fields. Our results reveal the electric fields and their variability at the group level in the standard brain space, providing insights into the mechanisms of tDCS for plasticity induction. The data are useful for planning, analysing and interpreting tDCS studies. •Electric fields of transcranial direct current stimulation are studied in 62 individually constructed head models.•Maps of group-level electric field and its variability are presented on the standard brain for 16 electrode montages.•Brain regions with both low and high inter-subject variability in electric fields were revealed.•Frontal tDCS has more variable electric fields than motor cortical tDCS.•Group-level electric field maps help planning and analysing tDCS.